UN Decade of the Ocean for Sustainable Development. Issue 1 (1st November 2021) - Rader, Lauren; Achilles, Kate; Christopher, David; Payne, Diana
In 2015, the United Nations (UN) adopted the 2030 Agenda for Sustainable Development. As part of this visionary blueprint for improving the lives of people all around the world, the UN outlined measurable goals to assess the impacts of the Agenda. NMEA has participated in important and relevant Decade activities when possible or invited, and NMEA will continue to play a role in UN Decade activities as they become available.